Balancing Forensic Technology and Human Rights in the International Legal Framework and Financial Crime Context: A Legal Analysis - Malik, Ghulam Mujtaba; Memon, Hyder Ali; Ahmed, Taniya (Annals of Human and Social Sciences, 2025)
This study examines the impact of forensic technologies on human rights within the context of international law, focusing specifically on financial crime investigations involving digital evidence. It is delimited to legal and ethical implications under major international instruments.Forensic tools such as digital evidence extraction, network forensics, and big data analytics have enhanced the detection of complex financial crimes. However, their increasing use raises critical concerns over privacy, data protection, and due process. International frameworks, including the GDPR, UNCAC, and the Budapest Convention, seek to balance investigative powers with fundamental rights. A doctrinal research approach combined with qualitative analysis was applied to review legal texts, scholarly literature, and case studies. Findings reveal gaps in global regulatory consistency, inadequate ethical oversight, and risks of rights violations in cross-border digital investigations. Stronger scientific validation and ethical frameworks are urgently needed.The study advocates harmonised international standards, proactive regulation of AI-based forensic tools, and integration of ethical oversight to ensure rights-compliant financial crime investigations.